Penerapan Model Pembelajaran Kooperatif dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Ilmu Pengetahuan Sosial - Julinar Julinar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2014)
This study uses an action research in implementing a ‘picture to picture’ model of cooperative learning in the teaching-learning of Social Sciences. The learning model can provide an opportunity for pupils to try and interpret the materials, ideas and opinions in line with their capability and potency through observation and interpretation media of images. The research was conducted to 25 of pupils grade 3 at the Primary School of Tanah Baru in Regency of Southeast Aceh in the school year of 2012/2013, with the subject matter regarding natural and artificial environments. As in knowing in teaching, Standard of Competency and Basic Competency of Social Science is full of materials with a wider and memorized scope. It causes lower achieving in learning at the school, showing by monthly test as its result of 83,34 percent pupils obtained the Minimal Passing Score. While only 16,67 percent of them reached Minimal Passing Score with the average score of 4,83. Based on the finding, it could be concluded that the ‘picture to picture’ model of cooperative learning impacts positively in elevating pupils achievement in learning marked by increasing in passing of learning on every cycle, such as 64.00 percent in the first , 76.00 in the second and 88.00 percent in the third cycle.